Cognitive dysfunction after on-pump Coronary Artery Bypass Grafting (CABG) in a tertiary university hospital – a prevalence study - Lim, M.H.; Mohd Zuli Jaafar,; Rufinah Teo,; Nadia Md Nor,; Muhammad Ishamuddin Ismail,; Joanna Ooi Su Min,; Aliza Mohamad Yusof, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Postoperative cognitive dysfunction (POCD) was a common complication of onpump coronary artery bypass grafting (CABG) which could reduce the quality of life. We investigated the prevalence and perioperative risk factors associated with POCD after elective CABG surgery. In this prospective cross-sectional study, 38 patients were recruited and their cognitive function was assessed using Montreal Cognitive Assessment (MoCA) at preoperative, 7th and 30th days, postoperatively. A total of 34 patients completed the study with four dropouts due to post-operative death.Prevalence of POCD on the 7th day and 30th days were comparable at 41% and 26.4%, respectively. The preoperative mean MoCA scoring improved significantly in patients with POCD on the 7th and 30th day after CABG surgery (24.68 + 3.57 vs 25.06 + 3.73 vs 25.88 + 4.00, p-value 0.044). Higher age was correlated with a reduction in mean MoCA score and increased risk of POCD detected on the 7th and 30th day postoperatively (Rs -0.451 and -0.359, p-value 0.007 and 0.037, respectively). Patients with abnormal lung function tests had a significant reduction of MoCA scoring at preoperative and lower improvement score postoperatively, compared with normal lung function test patients (p-value 0.013). In conclusion, POCD after on-pump CABG surgery occured in about one-third of the patient and improved over time. Increasing age and abnormal preoperative lung function tests were identified as the risk factor for POCD. Abnormal lung function test was associated with a lesser one-month cognitive improvement after CABG.